New sources of agriculturally valuable traits in hemp from the VIR collection for cultivar development - S. V. Grigoryev (Труды по прикладной ботанике, генетике и селекции, 2019)
Background. Modern hemp cultivation and processing are targeted at the production of textiles for various purposes, hurds, seeds and oil for functional food and pharmaceutical use. The import of textiles to Russia has been observed to grow continuously, reaching $8.96 billion in 2016–2017. The present industrial hemp production in Russia is still a source of textile yarn, integrated in the industrial turnover of goods in the Russian Federation. There are 27 cultivars and hybrids of industrial hemp for universal and dual use listed in the Russian Register of Breeding Achievements. However, there are no registered cultivars specifically earmarked to produce seeds or high-quality oil with improved fatty acid profile for production of functional food ingredients. Hemp genetic resources, as a reserve stock for crop improvement in the world’s plant breeding centers, are quite scanty and genotypically similar, and their major useful traits have practically not been evaluated. Thus, accumulation of hemp germplasm variable in traits, its evaluation and screening to identify sources of such characters as earliness and high seed yield should be prioritized for further progress in the development of new cultivars on a broader genetic base. Materials and methods. Accessions of Cannabis sativa L. of the Mid-Russian and Northern ecotypes were studied under the edaphoclimatic conditions of Russia’s northwest at Pushkin and Pavlovsk Laboratories of VIR with the purpose to assess the following traits: ripening of female and male plants 100 days after sowing (scores), seed yield per female plant, technical plant lengths, and correlations between plant sex types. Results and conclusions. The accessions k-528 (Tyumen), k-413 (Kazakhstan), k-313 (Kirov), k-151 (Mari), k-315 (Kirov), k-316 (Kirov), k-317 (Kirov), and k-132 (Ukraine) were characterized as early-ripening (female plants). Accessions similar in earliness of female plants, but differing in earliness of male plants (early, medium early and late) were identified. Medium and late male plants, as well as late female ones, are needed for the development of CBD-rich conventional dioecious cultivars. The accessions k-88, k-317 and k-351 were selected for earliness in female plants and medium earliness in male ones as well as for comparatively high seed yield per plant; they may be used in breeding programs to develop cultivars specifically for palatable seeds, which would make high-quality functional food ingredients due to their polyunsaturated fatty acid (PUFA) profile.